Взаимосвязь между электронными параметрами атома азота и внутримолекулярными взаимодействиями в производных аммиака - Чертихина, Ю. А.; Куцик-Савченко, Н. В.; Лебедь, О. С.; Либ, А. С.; Цыганков, Александр Валерьевич; Просяник, А. В. (Украинский государственный химико-технологический университет, 2019)
The electronic parameters and intramolecular interactions in the ground and transition states of inversion of the amines H₂NXHn (XHn=CH₃, NH₂, OH, F, SiH₃, PH₂, SH, Cl) were calculated using DFT (PBE96/def2-tzvpp) method. It was established that the electronacceptor properties of the XHn substituents has a prevailing influence on the change of the electronic parameters of nitrogen atom. Its increase leads to both a decrease of the charge on the nitrogen atom and an increase of the s-character and population of nitrogen lone pair (LP). All parameters under consideration correlate with the χ- and σᵢ-constants of the XHn substituents. The correlation coefficients increase when amines that contain X atoms only from one period are considered separately. It was found that the ρ values for amines containing X atoms from the second or third period are substantially different. The changes of the donor-acceptor interaction energies, s-character and LP population cannot be probable causes for different sensitivity of the electronic parameters of amines containing X atoms from different periods to the change of electron-acceptor properties of the XHn substituents. It was established that the mentioned parameters has only a subordinated influence in comparison with the influence of electron-acceptor ability of the XHn substituents. The negative charge on the nitrogen atom decreases with the increase of s-character and LP population and also with the decrease of energies of donor-acceptor interactions which lead to the withdrawal of electron density from the nitrogen atom. The s-character and LP population increase with the decrease of energies of donor-acceptor interactions which result in the reduction of electron density on the nitrogen atom. The total positive charges of the XHn groups and hydrogen atoms at the nitrogen atom decrease with increasing the electron-acceptor ability of the XHn substituents. The representation of the electron-acceptor properties of the substituents was shown to be more valid by using the χ-constants than by using the σᵢ-constants. The chlorine atom is a weak electron acceptor in comparison with an amino group.
The interrelation between the electronic parameters of nitrogen atom and intramolecular interactions in ammonia derivatives
Keywords: амины; инверсия; электроотрицательность; заряд; корреляционный анализ; amine; inversion; intramolecular interaction; electronegativity; charge; correlation analysis